Globalization of Leadership Development An Empirical Study of Impact on German and Chinese Managers - Wang, Jingjing; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2015)
It is generally understood that some effective leadership behaviors of Chinese managers differ from those of Western managers. It has also been debated controversially whether Chinese learners can benefit from Western learning approaches. Taking these two aspects into consideration, Jingjing Wang examines whether a global leadership development program from Western countries has as much impact on Chinese managers as on Western managers. She conducts the empirical study within one global corporation originating from Germany and the data were collected from Germany and China. Based on the core results of the study, implications for the globalization of leadership development are discussed. Contents Effective Leadership and Cross-Cultural Variation German and Chinese Culture and Leadership Learning Approaches for Leadership Development Programs Impact of Leadership Development Programs Multi-Perspective Rating A Global Leadership Development Program Target Groups Researchers and students of business administration, management, psychology, adult education, and sociology Executives, coaches, trainers and consultants of leadership development in a global context The Author Dr. Jingjing Wang received her Ph.D. at the faculty Human Resources Management and Leadership at the University of Bayreuth. Currently she works as a trainer and consultant for the Corporate Academy of a car manufacturer in Stuttgart.
Effective Leadership and Cross-Cultural Variation -- German and Chinese Culture and Leadership -- Learning Approaches for Leadership Development Programs -- Impact of Leadership Development Programs -- Multi-Perspective Rating -- A Global Leadership Development Program.
Keywords: Economics; Economics/Management Science; Human Resource Management; Emerging Markets/Globalization.; Business Strategy/Leadership.